2013
DOI: 10.1093/ndt/gft238
|View full text |Cite
|
Sign up to set email alerts
|

Patient perspectives on informed decision-making surrounding dialysis initiation

Abstract: A majority of patients felt unprepared and ill-informed about the initiation of dialysis. Improving the extent of IDM about dialysis may optimize patient preparation prior to starting treatment and their perceptions about the decision-making process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
156
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(161 citation statements)
references
References 39 publications
5
156
0
Order By: Relevance
“…As early as 2000, the Renal Physicians Association and the American Society of Nephrology released a guideline recommending SDM as critical to decisions around initiation and withdrawal from dialysis (74,75). However, studies suggest that SDM has not been widely implemented in treatment decisions (76), and the need for development and evaluation of decision aid tools for CKD remains (77,78). In response, Boulware and colleagues (79) developed Providing Resources to Enhance Patients' Readiness to Make Decisions about Kidney Disease, a decision aid program addressing key patient concerns-morbidity/mortality, autonomy, treatment delivery, symptoms, relationships, psychologic wellbeing, and finances-to help patients and their providers work together to choose a kidney failure treatment that best meets the patients' needs.…”
Section: Innovative Approaches To Ckd Educationmentioning
confidence: 99%
“…As early as 2000, the Renal Physicians Association and the American Society of Nephrology released a guideline recommending SDM as critical to decisions around initiation and withdrawal from dialysis (74,75). However, studies suggest that SDM has not been widely implemented in treatment decisions (76), and the need for development and evaluation of decision aid tools for CKD remains (77,78). In response, Boulware and colleagues (79) developed Providing Resources to Enhance Patients' Readiness to Make Decisions about Kidney Disease, a decision aid program addressing key patient concerns-morbidity/mortality, autonomy, treatment delivery, symptoms, relationships, psychologic wellbeing, and finances-to help patients and their providers work together to choose a kidney failure treatment that best meets the patients' needs.…”
Section: Innovative Approaches To Ckd Educationmentioning
confidence: 99%
“…In a large survey of .2000 patients, ,25% of patients indicated that heath care providers gave "excellent" information when choosing HD or PD (6). Other large studies also found that a significant proportion of patients (approximately 40%-65%) felt that they did not have a choice in dialysis modality or that they were not informed of their choices (7,8) (choice A is incorrect). However, patient involvement in modality decision making is associated with greater patient satisfaction once on dialysis (8).…”
Section: Discussion Of Question 1amentioning
confidence: 99%
“…Many patients receiving hemodialysis express a desire to know their treatment options, as well as their prognosis (13). Surveys and interviews of patients undergoing hemodialysis suggest that most patients believe they were not given sufficient information, or other viable choices, on their ESRD and hemodialysis (1,(12)(13)(14)(15)(16). We believe that this needs to change and that regular, iterative exploration of patients' goals of care can effect this change.…”
Section: Preserving Patient Autonomymentioning
confidence: 99%
“…We concluded that a narrow interpretation of beneficence that focuses only on life extension fails to consider that many elderly patients have other goals and priorities that are equally if not more important to them (7,8). Although major professional societies (9,10) and the Institute of Medicine (11) recommend that patients' goals and values be used to guide treatment recommendations (10), this is not consistently done, particularly for high-risk or frail elderly patients (1,7,(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%